Distinguishing midzonal iris pigment epithelial cyst from adenoma and ciliary body melanoma - Mayro, Eileen L. (Oman J Ophthalmol, 2018)
A 49-year old male with corrected visual acuity of 20/25 OD and 20/20 OS was found to have an asymptomatic dark iris mass OD with suspicion for ciliary body melanoma. Predilation slit-lamp biomicroscopy revealed a well-circumscribed brown round mass arising posterior to the iris, presumably from the ciliary body; however, postdilation demonstrated an extended fusiform mass of the iris pigment epithelium (IPE). By anterior segment imaging, the well-circumscribed IPE mass was cystic and measured 1440 microns in thickness peripherally predilation and 300 microns in thickness postdilation. There was no solid IPE or ciliary body component. A diagnosis of midzonal IPE cyst was rendered and observation advised. Clinical features and anterior segment imaging can assist in differentiation of midzonal IPE cyst from adenoma and ciliary body melanoma. The diagnostic methodology described in this paper can be used by ophthalmologists to promptly rule out underlying melanoma.